Groups of Deixis in Song Lyrics Say it Right By Nelly Furtado - Handayani, Chintia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this inquire about is to discover out types of the deixis and the foremost overwhelming deixis utilized in tune lyrics 'Say it Right' by Nelly Furtado. Nelly Furtado could be a Canadian vocalist for the song 'Say it Right'. The strategy utilized may be a clear subjective since the information are within the frame of words and expressions. The source of the information was taken from 'Say it Right' verses song. After examining the information, the result of this investigate is 69 information. Persona deixis (58 information), spatial deixis (7 information), and temporal deixis is (8 information). The foremost overwhelming that the analyst found in this investigate is persona deixis.